Toxicidade renal e hepática da tepoxalina em cães submetidos à hipotensão com isofluorano - Lopes, Carlize (2011)
This study aimed to evaluate the possible renal and hepatic toxicities, acute and subacute, of the administration of tepoxalin in dogs submitted to hypotension with isoflurane. A total of 12 dogs were used, which received 10 mg kg-1 of tepoxalin PO two hours before induction of hypotension (T) or were only submitted to hypotension with isoflurane (C). For the subacute study, animals in T were treated with tepoxalin during 5 days, following the hypotensive procedure. The dogs were submitted to hypotension (MAP= 50-60mmHg) for isoflurane in a circular circuit valve, with adjusted FR for the ETCO2 remained between 35-45mmHg. ToC was maintained between 37 and 38oC. HR, SAP, MAP, DAP, CVP, ETCO2 and ETIso were evaluated at 0, 10 and every 10 min up to 60min of hipotension. pH, PaO2, PaCO2, SaO2, HCO3-, BD, Na+, K+, Ca2+ and bleeding time evaluations were carried out before hypotension and at 30 and 60min of hipotension. For renal and hepatic evaluation, serum levels of U, Cr, ALT, alkaline phosphatase, GGT and urinary levels of GGT, Cr and GGT:Cr ratio were determined at 12h, 24h and seven days after the procedure. During the anesthetic procedure, only CVP presented elevation in relation to 0min in both groups at 50 and 60min of evaluation. In blood gas and electrolyte measurement, only Na+ presented levels below to basal at 60min in T, and this same group showed increased values at all intervals, in comparison between groups. Moreover, bleeding time was shown to be more elevated at 30min of evaluation in animals in T, when compared to the ones in C. The variables corresponding to creatinine depuration, GGT:Cr ratio and UV remained stable during the evaluations; however, urinary GGT levels presented increased values in animals in C when compared to T, at 60min of evaluation. At this same interval, urinary Cr values were elevated in T. Serum levels of ALT, alkaline phosphatase, U and Cr presented minor alterations, remaining within reference values; however, GGT presented increased values at 60min of evaluation, when compared to 0min. On the seventh day of evaluation, a reduction in leukocyte number was observed in animals in T, when compared to C. Side effects were not observed in both groups. The prior administration of tepoxalin in healthy dogs submitted to hypotension did not cause significant effects upon renal and hepatic functions. Moreover, daily administrations during five days, following the anesthetic procedure, did not alter the functions of the organs mentioned. Therefore, tepoxalin showed to be a safe NSAID to be used in healthy dogs, submitted to hypotension during anesthesia with isoflurane.